Critique of Malay Manuscripts: A Philological Study of the Book Khutbah Muharram Month by Guru Haji Ismail Mundu (1870 – 1957 AD) - Reno Piansyah; Faizal Amin; Nelly Mujahidah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to conduct a philological study of the Malay manuscript entitled Kitab Khutbah Bulan Muharram by Guru Haji Ismail Mundu (1870 - 1957 AD). This research is motivated by the importance of preserving the Malay manuscript heritage as an intellectual and spiritual source of the archipelago, especially in West Kalimantan. The methods used include physical inventory of manuscripts, cataloging studies, digital photography, and text variant analysis to produce a clean and critical edition of the text. The results of the discussion of physical condition are still good even though there are stains and translucent ink, as well as neatly sewn and stored in a pest-proof box. The text description reveals that the sermon structure consists of praise to Allah, salawat to the Prophet, advice on fasting the ten Muharram, and the story of the martyrdom of Husain bin Ali, presented in Arabic-Malay letters. Researchers also highlighted a number of reading variants and writing of Arabic terms that need to be standardized. These findings are important to provide a philological edition that can be used as a reference for further studies in the field of Malay culture and religion.